Alocação e tempo em trabalho não agrícola de residentes rurais no Brasil: uma análise por macrorregiões - Estanislau, Patricia (2021)
The main objective is to analyze the characteristics that determine workers residing in rural areas to join and allocate hours in non-agricultural activities. Demographic, physical capital, locational and social attributes were analyzed. The database used comprises microdata from the 2015 Pesquisa Nacional por Amostra de Domicílios (PNAD). The theoretical model adopted shows the decision of agricultural workers to maximize their time between leisure, agricultural and non-agricultural activities. The Double Hurdle model was used - which comprises two stages (Probit and Tobit) to estimate the determinants for adherence and hours destined for agricultural activity, respectively. The rural population in non-agricultural activity is 5.456.047 people with 56.22% men, the Northeast is the region with the most people employed in this work activity with 2.309.428. Most workers consider themselves brown, the average age and experience is higher for men, however women have more education. Family heads involve 33.94% of men. The lack of access to water and electricity affects men more, on the other hand, they are more connected to the internet. The service sector is the one that employs the most. The manufacturing industry is more intense in the South and Northeast. Weekly hours are higher for men, and incomes are higher in the Southeast. If all rural residents had income, the estimated share in 2015 would be 1.04% of PIB. In the Double Hurdle model, for both sexes and regions, retirees do not adhere to and allocate hours to non-agricultural activities and schooling works as a driver for rural residents to adhere to and allocate non-agricultural hours. In the first stage of the Double Hurdle model for women, women with no income from the North and Northeast tend to engage in non-agricultural activities, have more experience (Midwest and North), higher education (Northeast, Southeast), are spouses (Northeast), are family heads (Brazil, South, Southeast and Northeast). Being affiliated with unions (Northeast), having electricity supply (South) and living close to urban areas or in rural areas contributes positively to non-agricultural activities. In the second stage of the women's model, it was estimated that having a car (Brazil) means that there is greater allocation of non-agricultural hours. For the first stage of the Double Hurdle model for men, the hourly wage is one of the determinants for adherence to non-agricultural activities, as well as being white and living in the Northeast; age in the North, Northeast and Brazil, access to internet in the Midwest and Northeast and living close to urban areas influence the choice of non-agricultural activities. In the second stage for men, it was estimated that having a car (except the Northeast) and living close to urban areas (Brazil) makes rural men spend more hours on non-agricultural activities, as well as being employed in industry for Brazil and in commerce (except in the South). Diversity and heterogeneity were observed in the Brazilian regions and between men and women in non-agricultural activities. The alleviation of poverty through self-consumption reduces the participation of men in non-agricultural activities, and if they do not have income, they seek income from non-agricultural activities, while for women these variables do not impact the decision to participate. There is no allocation of hours in non-agricultural activities with higher income due to low qualification for men and if women are in domestic activity. There is a need for research and public policies mainly aimed at women and gender equity, as well as improving the quality of the population's self-consumption. Policies to promote and stimulate local economies, integrate the labor market and family farming. The greater availability of employment and income for the rural population helps in rural development.